Effect of tillage practices on yield and energy use pattern of clusterbean (Cyamopsis tetragonoloba L. Taub) - pearl millet (Pennisetum glaucum L. R. Br.) rotation in arid zone - Patidar, M; Singh, A K (Journal of Agricultural Engineering, 2006)
A study was conducted on different tillage practices for growing clusterbean-pearl millet rotation in sandy soils of arid zone. The results indicated that grains yield of clusterbean and pearl millet ploughed with a cultivator at 22.5cm spacing (farmer's practice) was significantly lower than harrowing treatments. However, yield under modified farmer's practice i.e. planting in alternate row with cultivator tynes spaced at 22.5 cm was equivalent to that of harrowing treatments. Water use efficiency improved with increase in number of tillage operations and it was maximum with cross harrowing treatment. The energy use pattern revealed that disc harrowing (cross) consumed more energy(12715 MJ ha¯¹) and plough plant system consumed less energy (10477 MJ ha ¯¹). The treatment cultivator (one run) gave highest output-input ratio 13.1 followed by disc harrowing (one run) 12.9 output-input ratio. The specific energy was lowest with disc harrowing (one run) 4.9 MJ kg¯¹ grain followed by cultivator one run (5.0 MJ kg ¯¹ grain). This shows that the minimum tillage practices, namely; cultivator (one run) and disc harrowing (one run) are more energy efficient as compared to either plough plant system or disc harrowing (cross in sandy soils of arid zone.